Kombinasi Optimal cara Olah Tanah dan Tingkat Pengapuran untuk Pola Tumpangsari Jagung di antara Karet pada Tanah Podzolik Merah Kuning - Gede Wibawa; Heru Suryaningtyas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2001)
Technical modification of rubber based intercropping system are still needed due to the appearance of various problems, either bio-physical or socio-economie factors. At different areas, where labour is limited, substitution of  manual tillage and manual seeding with mechanical equipment and manual weed control with chemical control has to be taken into account. Research on rubber based intercropping, combining two tillage systems. Conventional or full tillage, where soil was plowed and harrowed 2 and 2 times respectively,. and reduced tillage where soil tillage was done only one plowing and one harrowing and four liming levels atintercrop rows at 20 cm with (maize, variety of C7) was carried out in Sembawa Research Institute since 1998. The presented data were collected tillage system and liming dose was observed, however the grain yield difference was reduced up to 22%. During dry season cowpea (Vigna anguikulata), planted after maize, produced 870 kg/ha. The cost of production of cropping maize as rubber intercrop using full tillage system at optimal liming level was about Rp. 2,1 million. If the grain price is Rp. 1200/kg then the break-even point will be reached at grain yield of 1750k g/Ha. Rubber growth of IRR 39 clone, a latex and timber clone, was very good. Until 13 months stem diameter was  not affected by tillage systems and levels of liming for intercrop. Key words: Intercropping, Rubber, Maize, Cowpea, Soil tillage, Liming, Ultisol